Ternary Blend Solar Cells Based on a Conjugated Polymer With Diketopyrrolopyrrole and Carbazole Units - Wang, Yanbin; Chen, Jinxing; Kim, Hyung Do; Wang, Biaobing; Iriguchi, Ryo; Ohkita, Hideo (Frontiers in Energy Research, 2018)
Herein, we have synthesized a low-bandgap polymer (PCDPP4T) consisting of diketopyrrolopyrrole (DPP) and carbazole (Cz) units in the main chain. The absorption coefficient is as high as 1.3 × 105 cm−1 for PCDPP4T, which is slightly higher than 1.0 × 105 cm−1 for the monomer model compound (DPP4T-Cz). For ternary blend solar cells based on poly(3-hexylthiophene) (P3HT), [6,6]-phenyl-C61-butyric acid methyl ester (PCBM), and only 3.4 wt% of PCDPP4T, the photocurrent increased and thus the power conversion efficiency (PCE) was improved by 30% relative to those of P3HT/PCBM binary reference cells. The improved photocurrent was ascribed partly to a complementary absorption of PCDPP4T in the near-infrared (near-IR) region, and partly to an efficient energy transfer from P3HT to PCDPP4T. We also discuss the origin for the improved photocurrent and requirements for further improvements.